2003
DOI: 10.1038/sj.bjc.6601029
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl benzylamide dextran inhibits angiogenesis and growth of VEGF-overexpressing human epidermoid carcinoma xenograft in nude mice

Abstract: Vascular endothelial growth factor (VEGF) expression is elevated in a wide variety of solid tumours. Inhibition of VEGF activities is able to reduce angiogenesis and tumour growth. We have recently shown in vitro that carboxymethyl dextran benzylamide (CMDB7) prevents the binding of VEGF 165 to its cell surface receptors and thus inhibits VEGF activities on endothelial cells. In the present study, we explored the effects of CMDB7 on highly aggressive human epidermoid carcinoma A431 cells known to overexpress e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…To visualize intratumor endothelial cells (ECs), sections of 5 mm were specifically stained with GSL-1 lectin (Vector, Burlingame, California, USA) as previously described [17][18][19]. To visualize intratumor endothelial cells (ECs), sections of 5 mm were specifically stained with GSL-1 lectin (Vector, Burlingame, California, USA) as previously described [17][18][19].…”
Section: Tumor Cell Inoculation In Nude Micementioning
confidence: 99%
See 1 more Smart Citation
“…To visualize intratumor endothelial cells (ECs), sections of 5 mm were specifically stained with GSL-1 lectin (Vector, Burlingame, California, USA) as previously described [17][18][19]. To visualize intratumor endothelial cells (ECs), sections of 5 mm were specifically stained with GSL-1 lectin (Vector, Burlingame, California, USA) as previously described [17][18][19].…”
Section: Tumor Cell Inoculation In Nude Micementioning
confidence: 99%
“…Image analysis was performed using the Image analysis NIH program as previously described [17][18][19]. Image analysis was performed using the Image analysis NIH program as previously described [17][18][19].…”
Section: Tumor Cell Inoculation In Nude Micementioning
confidence: 99%
“…Circulating heparin-like sulphated polysaccharides can bind to heparin-binding domains of ECM proteins. As reported for heparin or other polyaromatic heparin-mimicking compounds [19,[35][36][37], the binding of heparin-like polymers could locally modulate the bioavailability of key regulatory components such as heparin-binding growth factors present in the ECM [38][39][40]. Similarly to synthetic polysaccharides that exhibited in vivo affinity for damaged muscular tissue after systemic injection [4], the increasing concentration of LMW fucoidan at the damaged vascular wall may lead to reduction of the restenosis rate.…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, it has been widely shown that activity of VEGF is a key feature during tumor growth and angiogenesis [28][29][30] . In the course of occurrence and development of gastric cancer, angiogenesis plays a crucial role in which VEGF is believed to be the most important factor in neovascularization [31] .…”
Section: Discussionmentioning
confidence: 99%